Formulation and Application of Organic Fertilizer from Cow Dung to Increase Rice Yield by Applying Sustainable Agriculture Principles in Gantiwarno, Klaten - Minardi, Slamet; Sudadi, Sudadi; Haniati, Isna Luthfa; Pramono, Sidik; Suryono, Suryono (PRIMA: Journal of Community Empowering and Services, 2022)
Livestock Farmer Group Lembu Mulyo was a cattle breeder engaged in livestock farming. Cow dung was a problem for breeders because of the large amount of cow dung that had not yet been utilized, causing air, water, and soil pollution. The Mentoring activity aims to overcome the problems faced by partners by utilizing cow dung waste from Livestock Farmer Group Lembu Mulyo could be used as organic fertilizer by the Farmer’s Group Sri Rejeki to increase rice yield by applying the principles of sustainable agriculture. The Livestock Farmer Group Lembu Mulyo problem could be solved by formulating organic fertilizer using cow dung. Furthermore, it could address the Farmer’s Group Sri Rejeki problem, which is an increasing need for fertilizer to increase rice yield by applying sustainable agriculture principles. The mentoring activity was in collaboration with two partners, namely the Farmer’s Group Sri Rejeki and the Livestock Farmer Group Lembu Mulyo, located in Gesikan Village, Gantiwarno District, Klaten Regency. The method used was socialization and practice. The result of the mentoring activity for formulating organic fertilizer was that the Livestock Farmer Group Lembu Mulyo could formulate organic fertilizer from cow dung, and the Farmer’s Group Sri Rejeki was able to apply an organic fertilizer to increase rice yield. The two partners’ capabilities could overcome problems in the Livestock Farmer Group Lembu Mulyo and the Farmer’s Group Sri Rejeki. In addition to solving the problems of the two partners by formulating organic fertilizers and their application in rice fields also applied sustainable agriculture principles.